Transformative learning in graduate education: masters of social work students' experiences of personal and professional learning. Issue 9 (1st September 2020) - Damianakis, Thecla; Barrett, Betty; Archer-Kuhn, Beth; Samson, Patricia L.; Matin, Sumaiya; Ahern, Christine
ABSTRACT: Transformative learning captures the process by which students engage in their learning at holistic levels (emotional, cognitive, spiritual, physical, social, and environmental) and the extent to which they experience a change in perspective, of themselves or society. This four-year, four-cohort study ( n  = 40) examined the transformative learning experiences of Masters of Social Work students as they prepared to graduate and practice in their professional field. Data were collected via focus group methods and were analyzed using qualitative content analysis. Three primary themes were identified: (1) transformation is a process of feeling displaced, re-evaluating, and surfacing; (2) transformative outcomes are multidimensional and embody personal and professional learning; and (3) transformative learning is a holistic experience. This study makes a novel contribution to the literature on transformative learning by empirically examining students' experiences of transformation within accredited professional programs, and the development of pedagogical approaches that facilitate student growth within such settings.